2020
DOI: 10.1002/casp.2495
|View full text |Cite
|
Sign up to set email alerts
|

Programme and school predictors of mentoring relationship quality and the role of mentors' satisfaction in volunteer retention

Abstract: The quality of the mentor–mentee relationship is considered the key mechanism of change in mentoring programmes, and volunteer mentor retention is crucial to improving delivery and outcomes. Combining theoretical frameworks on mentoring programmes and volunteerism, this study aimed to examine: (a) programme and school predictors of mentoring relationship closeness and (b) the relations between mentor‐reported relationship closeness, satisfaction with the relationship as a measure of subjective evaluations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…The mediated path models indicated the strength of the mentor-staff relationship, as represented by bonding and agreement in their working alliance, was associated with all indicators of mentoring relationship quality. These results accord with previous research findings that mentor perceptions of positive support from program staff correspond to satisfaction with and continuation of mentoring relationships (Aresi et al, 2021;McQuillin et al, 2015;Sass & Karcher, 2013;Weiler et al, 2019) and with research indicating the approaches employed by staff in working with mentors contribute to mentoring relationship quality (Keller & DuBois, 2021;Marshall et al, 2016). Associations between the mentor-staff working alliance and the relationship interaction outcomes, including negativity, may reflect that ongoing support through staff contacts with the mentor could be more responsive and relevant to what is actually occurring in the mentoring relationship than standard program practices (Marshall et al, 2016).…”
Section: Staff-reported Program Practicessupporting
confidence: 92%
“…The mediated path models indicated the strength of the mentor-staff relationship, as represented by bonding and agreement in their working alliance, was associated with all indicators of mentoring relationship quality. These results accord with previous research findings that mentor perceptions of positive support from program staff correspond to satisfaction with and continuation of mentoring relationships (Aresi et al, 2021;McQuillin et al, 2015;Sass & Karcher, 2013;Weiler et al, 2019) and with research indicating the approaches employed by staff in working with mentors contribute to mentoring relationship quality (Keller & DuBois, 2021;Marshall et al, 2016). Associations between the mentor-staff working alliance and the relationship interaction outcomes, including negativity, may reflect that ongoing support through staff contacts with the mentor could be more responsive and relevant to what is actually occurring in the mentoring relationship than standard program practices (Marshall et al, 2016).…”
Section: Staff-reported Program Practicessupporting
confidence: 92%
“…Quantitative findings have consistently noted a positive relationship between RQ, closeness, and duration and desired outcomes (Cavell et al, 2009; DeWit et al, 2016; DuBois & Karcher, 2005). Studies have found that mentor reports of relationship satisfaction and perceptions of the match mediate mentor retention and commitment (Aresi et al, 2012; McQuillin et al, 2015).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Study participants seemed to seek support, encouragement and guidance from people close to them primarily when subject to an excessive emotional burden and/or when they perceived they had reduced access to discussions with the PC. Also, as well‐known (Aresi et al, 2021; Caldarella et al, 2010; Gettings & Wilson, 2014), mentors—although unsatisfied—may feel pushed to persevere due to the desire not to let down the mentee. The sense of “normative commitment”—widely detected among interviewed mentors—may be simply reflective of how strongly other‐oriented they are or, alternatively, cast some doubts on the amount of personal benefits volunteers derived.…”
Section: Discussionmentioning
confidence: 95%
“…With respect to the contact with school personnel, prior research has brought mixed results. For instance, Aresi et al (2021) found teacher support to be unrelated to mentors' self‐report of the MR quality. By contrast, Raven (2015) saw these stakeholders as vital to the success of SBM programs, as their feedback can help mentors recognize improvements in the mentee's behaviors, attitudes or academic achievements, boosting their confidence and sense of accomplishment.…”
Section: Discussionmentioning
confidence: 99%